Posibilidades y alcances del mejoramiento genético basado en mutación inducida en yuca (Manihot esculenta Crantz) - Tofiño Rivera, Adriana Patricia; Romero, HM; Fregene, Martin A.; Rosero, Elvia Amparo (2007)
Cassava is a root crop and the third most important source of calories in the tropics. Production constraints include biotic and abiotic stresses. Farmers success in marketing their cassava has also fallen well short of its potential due to problems such as rapid post-harvest deterioration and inadequate starch and protein content in the roots. In addition, conventional genetic improvement programs are met with reproductive and breeding barriers, such as its allopolyploid nature, low fertility, low hybrid seed set, and poor germination rate. Such difficulties in incorporating useful and desirable traits in one genotype limit the possibility of obtaining new promising cultivars. Hence alternative ways to increase genetic variability are desirable. The new tools of advanced molecular biology, genetic engineering, and induced mutations, used in coordination with conventional plant breeding, can change this situation by offering new approaches to the challenges of cassava. Especially, the induction and selection of mutants provide a simple, efficient, rapid, and cheap method by which to alter the genetic make-up and obtain much more productive, nutritious, and profitable to grow genotypes from otherwise well-adapted genotypes.